On the exposure of the BRIC countries to global economic shocks - Ansgar Belke; Christian Dreger; Irina Dubova (Global Labor Organization (GLO), 2017)
The financial crisis led to a deep recession in many industrial countries. While large emerging countries recovered relatively quickly from the financial crisis, their performance deteriorated in the recent years, despite the modest recovery in advanced economies. The higher divergence of business cycles is closely linked to the Chinese transformation. During the crisis, the Chinese fiscal stimulus prevented a decline in GDP growth not only in that country, but also in resource-rich economies. The Chinese shift to consumption-driven growth led to a decline in commodity demand, and the environment became more challenging for many emerging markets. This view is supported by Bayesian VARs specified for the BRIC (Brazil, Russia, India, and China) countries. The results reveal a strong impact of international variables on GDP growth. In contrast to the other countries, China plays a crucial role in determining global trade and oil prices. Hence, the change in the Chinese growth strategy puts additional reform pressure on countries with abundant natural resources.
Keywords: F44; E32; C32; 330; Business cycle divergence; Chinese transformation; Bayesian VARs